Pengembangan KOPER (Kotak Permainan) untuk Materi Klasifikasi Makhluk Hidup di SMP - Dio Alfando; Darmanella Dian Eka Wati (Eduscience Development Journal, 2019)
Fun learning can increase students' learning desires. The game allows active participation both between students and teachers and vice versa, also between students and other students. Therefore we want to develop creativity and innovation talent to develop new games that can make students able to play while learning with the title "Development of Biology KOPER for Classification of Living Things in Middle School." The purpose of this study is to determine the validity and practicality. biology game media box for developed Living Classification material. This type of research is a research and development (Research and Development), using the product development model ADDIE (Analystys Desing Development Implementation Evaluation). The instruments used were questionnaire validity and practicality questionnaire. The test subjects in the study were 12 junior high school students at the Kamil learning house. Based on the analysis of the validity data of 3 validators, the average percentage of validity values is 90% with very valid criteria. Whereas the data from the practical questionnaire showed that the average percentage of practicality was 90% and included in the category of very practical. Based on these data it can be concluded that the learning media of biology game boxes is valid and practical to be used in studying the classification of living things in junior high schools.